ChemInform Abstract: Structure and Permanent Magnet Properties of Zr1‐xRxFe10Si2 Alloys with R: Y, La, Ce, Pr and Sm. Issue 36 (August 2016) - Gabay, A. M.; Cabassi, R.; Fabbrici, S.; Albertini, F.; Hadjipanayis, G. C.
Abstract: (Zr0.7 Ln0.3 )1.1 Fe10 Si2 (Ln: Y, Ce, Pr, Sm) alloys are prepared by arc melting and subsequent melt spinning.